Fresno County Bar Association Annual Bar Banquet at TorNino's - Watkins, Howard::::::::: (1985)
1985 Fresno County Bar Association President Donald Fischbach presenting plaque to Tomar Mason for her 3-years of service on the Fresno County Bar Association Board of Directors